Dormancy and germination of microsclerotia of Verticillium longisporum are regulated by soil bacteria and soil moisture levels but not by nutrients - Sarenqimuge, Sarenqimuge; Rahman, Shahinoor; Wang, Yao; von Tiedemann, Andreas (Frontiers in Microbiology, 2022)
The soil-borne pathogen Verticillium longisporum poses a serious threat to brassicaceous crops, including the economically important oilseed rape. The pathogen infects roots and systemically colonizes stems where it finally forms microsclerotia at crop maturity. Once returned into soil after harvest, microsclerotia undergo a stage of dormancy in which they may survive for several years. Since there is neither efficient chemical control nor effective resistance in oilseed rape cultivars available to control the disease, possible control strategies may consist in regulating the germination and dormancy of microsclerotia in the soil. Therefore, a series of experiments was conducted to explore the effects of nutrients, soil moisture and the soil microbiome on dormant microsclerotia. Under sterile conditions, the moisture level of the soil and the germination of microsclerotia were positively correlated. In contrast, under unsterile conditions, moisture levels had no such effect. Oilseed rape plants inoculated with microsclerotia of V. longisporum showed severe infection with V. longisporum when grown in autoclaved soil, in contrast to plants grown in unsterile soil. These experiments indicate a crucial role of soil fungistasis on microsclerotia germination. Further bioassays demonstrated that viable soil bacteria obtained from the rhizosphere of oilseed rape plants and from bulk field soil effectively inhibited microsclerotia germination, whereas dead bacteria and bacterial culture filtrates hardly suppressed germination. A putative inhibitory role of volatile organic compounds (VOCs) produced by soil bacteria was confirmed in two-compartment petri dishes, where microsclerotia germination and colony growth were significantly inhibited. VOCs were collected and analyzed by GC-MS. In total, 45 VOCs were identified, among which two acid and two alcohol compounds were emitted by all tested bacteria. A bioassay, conducted with corresponding pure chemicals, indicated that all acidic volatile compounds, including 3-methylbutanoic acid, 2-methylbutanoic acid, hexanoic acid and 2-methylpropionic acid, induced strong inhibitory effects on microsclerotia. We conclude that bacterial acidic volatiles play a key role in the fungistatic effect on microsclerotia of V. longisporum in the soil and could thus be targets for development of novel strategies to control this pathogen by artificially regulating dormancy of microsclerotia in soil.